2020
DOI: 10.1103/physrevb.101.020504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zeeman coupling on the Majorana vortex modes in iron-based topological superconductors

Abstract: In the superconducting regime of FeTe (1−x) Sex, there exist two types of vortices which are distinct by the presence or absence of zero energy states in their core. To understand their origin, we examine the interplay of Zeeman coupling and superconducting pairings in three-dimensional metals with band inversion. Weak Zeeman fields are found to suppress the intra-orbital spin-singlet pairing, known to localize the states at the ends of the vortices on the surface. On the other hand, an orbital-triplet pairing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Through spin-orbit coupling, the complex order parameter can induce spin magnetization as described in SI Appendix and explained in detail elsewhere (6). We note that alternative theories that may explain the appearance of the gap at the Dirac point have also been suggested (18,19). The presence of ferromagnetism in the surface region associated with strong spin-orbit coupling would potentially make this system an ideal platform for supporting a range of unique topological phenomena.…”
Section: Significancementioning
confidence: 85%
“…Through spin-orbit coupling, the complex order parameter can induce spin magnetization as described in SI Appendix and explained in detail elsewhere (6). We note that alternative theories that may explain the appearance of the gap at the Dirac point have also been suggested (18,19). The presence of ferromagnetism in the surface region associated with strong spin-orbit coupling would potentially make this system an ideal platform for supporting a range of unique topological phenomena.…”
Section: Significancementioning
confidence: 85%
“…This scenario offers a prediction of chiral Majorana modes located at the domain wall between these two spatially distinct phases. Another theoretical study suggested that Zeeman coupling from clustering of magnetic impurities may locally induce a superconducting orbital-triplet spin-singlet state near some vortices, thereby rendering those vortices non-topological and hence unable to support zero-energy MZMs [421]. [409].…”
Section: Experimental Evidence For Majorana Zero Modes: Vortex Statesmentioning
confidence: 99%
“…Recently, the threedimensional model has been extended to more specific circumstances, including 1) the vortex phase transitions in Fe(Te,Se) single crystals [198]; 2) the vortex phase transitions when the topological bands are coupled with trivial bands. In this case, the topological regime deforms, but still includes the Dirac points [199]; 3) the topological vortex phase transitions induced by Zeeman coupling [200]; 4) the topological vortex phase transitions of the weak topological insulator [201] and the Dirac semimetal [202,203].…”
Section: Picture Vortex Mzm: Two-versus Three-dimensional Modelmentioning
confidence: 99%